1983
DOI: 10.1128/iai.40.2.726-732.1983
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection of murine testicular interstitial Leydig cells

Abstract: We studied the susceptibility of mouse testicular interstitial Leydig cells to cytomegalovirus both in vivo and in vitro. The in vivo studies included intratesticular and intraperitoneal infection of 6-week-old mice with murine cytomegalovirus (MCMV); the in vitro studies involved an MCMV-Leydig cell interaction using a Leydig tumor cell line (1-10). MCMV-specific antigens were detected in interstitial Leydig cells in sections of MCMV-inoculated testes by an indirect immunofluorescence test. MCMV DNA was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…As with HCMV, MCMV infects a variety of organs and cell types. The spleen, liver, adrenal gland, salivary gland, kidney, lung, ovary, and testis have been shown to be infected (1,2,8,9,23,39,42,44), and in most cases, the infected cells appeared to be epithelial, interstitial, or parenchymal cells. Neurons are also infected by MCMV (13), and occasional infected endothelial cells have been observed (39,44).…”
mentioning
confidence: 99%
“…As with HCMV, MCMV infects a variety of organs and cell types. The spleen, liver, adrenal gland, salivary gland, kidney, lung, ovary, and testis have been shown to be infected (1,2,8,9,23,39,42,44), and in most cases, the infected cells appeared to be epithelial, interstitial, or parenchymal cells. Neurons are also infected by MCMV (13), and occasional infected endothelial cells have been observed (39,44).…”
mentioning
confidence: 99%
“…As an initial step in the determination of the origin of testicular infection and the susceptible cell types in the testes, we examined the interaction of MCMV with the testicular interstitial Leydig cells of mice. Our results indicated that Leydig cells are susceptible to MCMV both in vivo and in vitro (3). In this paper, we are reporting evidence that MCMV can replicate in sperm cells of immunologically competent mice.…”
mentioning
confidence: 74%
“…1). It also caused infection of the Leydig cells located in the testicular interstitial spaces, as shown in our previous report (3). The testes were examined by subjecting frozen testicular sections to in situ [3H]cRNA-DNA cytohybridizations (6, 13).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Likewise, Dutko and Oldstone (1979), using the same type of techniques, localized MCMV DNA in purified spermatozoa and in immature sperm cells, giving strong support to the argument of an acute and latent infection by MCMV of male germ-line cells. In addition, it was reported that interstitial Leydig cells of testicles are susceptible to MCMV infection both vivo and' in vitro (Baskar et al, 1983). These authors suggested the possibility that MCMV, by infecting Leydig cells, may upset hormonal balance and impede gametogenesis.…”
Section: The Gammaherpesvirinaementioning
confidence: 99%